Preventive health behaviors among people with suicide ideation using nationwide cross-sectional data in South Korea - Myung Ki; Hye-Young Shim; Jiseun Lim; Minji Hwang; Jiwon Kang; Kyoung-Sae Na (Scientific Reports, 2022)
Abstract This study aimed to investigate the association between suicide ideation and health-related behaviors and preventive health service use behaviors. We used data from the 2017 Korea National Health and Nutrition Examination Survey (KNHANES), a nationally representative survey. The final sample included 4486 participants aged 40 years or older. Preventive health behaviors were assessed for smoking, high-risk drinking, physical activities, regular meal intake, influenza vaccination, general health examination, and cancer screening. Logistic regression was used to examine the association between suicide ideation and preventive health behaviors with a series of adjustments for covariates. In general, suicide ideation was associated with unfavorable outcomes of preventive health behaviors, except for flu vaccination. For example, the adjusted prevalence of suicide ideation and non-suicide ideation groups were 54.3% vs. 43.7% for flu vaccination, 23.1% vs. 41.6% for physical activity, and 24.8% vs. 18.6% for high-risk alcohol drinking. After adjustment for covariates, the associations of suicide ideation with behaviors remained significant for physical activity (OR 0.52, 95% CI 0.34–0.81) and high-risk alcohol drinking (OR 2.22, 95% CI 1.34–3.69). Suicide ideation leads to the disruption of self-management of health behaviours, especially for physical activity and high-risk alcohol drinking, independently of depressive feelings.